The Effects of Mental Fatigue on Anaerobic Power and Power Endurance Performance - Matthew P. Gonzalez; Denver M. Y. Brown; Isabella M. Swafford; Bryce Summerville; Morteza Seidi; Marzieh Hajiaghamemar; Sandor Dorgo (MDPI AG, 2024)
Mental fatigue has been studied extensively in relation to its impact on aerobic-, strength-, and motor-based tasks, but anaerobic power-based tasks have received limited attention. Interdisciplinary research investigating the underlying mechanisms by which mental fatigue influences physical performance has been called for. In two studies, the effects of mental fatigue on maximal power jump and endurance jump performance as well as kinetics and kinematics during jump performance were examined. Samples of collegiate volleyball players (Study 1; N = 14) and recreationally active students (Study 2; N = 27) completed two 30 min experimental manipulations (high vs. low cognitive control exertion) before performing three maximal power squat jumps followed by 15 repeated countermovement jumps, with measurements of kinetics and kinematics. For Study 1, the maximal power performance was significantly lower under a mentally fatigued condition, but no differences were observed for repeated jump performance, which may have been attributable to alterations in jump mechanics. For Study 2, no between-condition differences were observed for the maximal power performance, although repeated jump performance was significantly lower under a mentally fatigued condition. Collectively, these findings suggest that the impacts of mental fatigue on power-based performance tasks may depend on the task demands as well as the training status of the individual.